'Funk Money': The End of Empires, The Expansion of Tax Havens, and Decolonization as an Economic and Financial Event. Issue 1 (23rd August 2020) - Ogle, Vanessa
Abstract: This article explores the question of what happened to European assets in the process of decolonization. It argues that decolonization created a money panic of sorts that led white settlers, businessmen, and officials to seek to liquidate assets they owned and move funds out of the colonial world. Instead of being repatriated to metropolitan countries with high tax rates and exchange controls, money moved to tax havens. Decolonization thus provided an important share of early postwar tax haven business in a period when tax havens and offshore finance expanded during the 1950s and 1960s. In turn, the withdrawal of Euro-American investments from the decolonizing world set the stage for the politics of development and modernization in the coming decades. Ironically, the outflow of funds during decolonization and the subsequent return of some funds in restructured form as investments by multinational and other companies soon caused difficulties in newly independent developing countries. Companies soon found ways to rebook profits to have occurred in a tax haven rather than in the developing world, thus depriving low-income countries from tax revenue. The withdrawal of Euro-American investments from the colonial world during decolonization moreover had implications for the growth of portfolio investment, as funds removed from colonies were often invested through a tax haven onwards in US securities. All in all, decolonization was an economic and financial event that is only beginning to emerge in full detail.